Kampungku Sehat: A Social Economic Impact Analysis on Community Based Empowerment: Kampungku Sehat: Analisis Dampak Sosial Ekonomi Pemberdayaan Berbasis Komunitas - Nauli Harahap, Reiki; A Ismail Lukman; Annisa Rizqa Alamri; Akhmad Rifky Setya Anugrah; As'ad Albatroy Jalius; Kanita Khoirun Nisa (Progress In Social Development, 2023)
The discourse and practices of corporate social responsibility continues to increase. Business entities are no longer only required to carry out corporate social responsibility activities but are urged to measure the impact of various CSR programs that have been carried out. Therefore, researchers are interested in conducting a study of the socio-economic impact on the company's CSR programs. This research was conducted in Yogyakarta, precisely the Kampungku Sehat: Kompak Maju’s program. The program is one of the CSR programs of PT Pertamina (Persero) DPPU Adisutjipto. This study used quantitative methods (surveys) and interviewed thirteen respondents. The results of the study concluded that the Kampungku Sehat: Kompak Maju’s program has “good” level and feasibility with an index value of 2.97 and a value conversion of 74.21%. This indicates that the program is successful with minor improvements or adjustment and allows it to be continued and disseminated as a best practice for other business entities. Diskursus dan praktik corporate social responsibility (CSR) terus mengalami peningkatan. Perusahaan tidak lagi hanya dituntut untuk melakukan aktivitas tanggung jawab sosial perusahaan saja, melainkan didesak untuk melakukan pengukuran dampak terhadap berbagai program CSR yang telah dilakukan. Oleh karena demikian peneliti tertarik untuk melakukan kajian dampak sosial ekonomi terhadap program-program CSR perusahaan. Penelitian ini dilakukan di Yogyakarta, tepatnya program Kampungku Sehat: Kompak Maju. Program tersebut merupakan salah satu program CSR PT Pertamina (Persero) DPPU Adisutjipto. Penelitian ini menggunakan metode kuantitatif (suvei), dan mewawancarai tiga belas responden yang merupakan seluruh penerima manfaat program. Hasil penelitian diperoleh kesimpulan bahwa program pemberdayaan Kampungku Sehat: Kompak Maju memiliki feasibilitas yang baik dengan nilai indeks 2.97 dan konversi nilai 74.21%. Hal tersebut menandakan bahwa program berhasil dengan sedikit perbaikan dan memungkinkan untuk dilanjutkan serta disebarluaskan sebagai sebuah best practices permberdayaan berbasis komunitas.